(untitled) (UNIZIK Journal of STM Education, 2025)
This study investigated the impact of discovery learning method (DLM) on students’ learning outcomes in chemistry, in light of technological advancement and economic meltdown. Four research questions and four null hypotheses were formulated to guide the study. Using a quasi experimental research design. The population consists of all SS2 chemistry students in the twenty-nine (29) government owned senior secondary schools in Ogidi education zone in Anambra State. A sample size of 164 SS2 students was randomly selected from four co educational secondary schools in two local governments in the area. Chemistry Achievement Test (CAT), developed by the researchers, was used as the instrument for data collection. The reliability of the instrument was established using the Kuder-Richardson formula 20. The reliability coefficient obtained was 0.82. While the research questions were answered using mean and standard deviation, the null hypotheses were tested at a 0.05 level of significance using two-way Analysis of Covariance (ANCOVA). The results showed that DLM has a significant impact on students’ academic achievement and knowledge retention in Chemistry, with a statistically significant gender impact on students’ achievement in Chemistry in favour of males. Furthermore, the discovery method does not have any statistically significant gender impact on students’ knowledge retention in Chemistry. Conclusions and recommendations were, however, made.